Therapeutic Effect of Benidipine on Medication-Related Osteonecrosis of the Jaw - Ken Matsunaka; Mikio Imai; Koma Sanda; Noriyuki Yasunami; Akihiro Furuhashi; Ikiru Atsuta; Hiroko Wada; Yasunori Ayukawa (MDPI AG, 2022)
Medication-related osteonecrosis of the jaw (MRONJ) is an intractable disease that is typically observed in patients with osteoporosis or tumors that have been treated with either bisphosphonate (BP) or antiangiogenic medicine. The mechanism of MRONJ pathogenesis remains unclear, and no effective definitive treatment modalities have been reported to date. Previous reports have indicated that a single injection of benidipine, an antihypertensive calcium channel blocker, in the vicinity of a tooth extraction socket promotes wound healing in healthy rats. The present study was conducted to elucidate the possibility of using benidipine to promote the healing of MRONJ-like lesions. In this study, benidipine was administered near the site of MRONJ symptom onset in a model rat, which was then sacrificed two weeks after benidipine injection, and analyzed using histological sections and CT images. The analysis showed that in the benidipine groups, necrotic bone was reduced, and soft tissue continuity was recovered. Furthermore, the distance between epithelial edges, length of necrotic bone exposed in the oral cavity, necrotic bone area, and necrotic bone ratio were significantly smaller in the benidipine group. These results suggest that a single injection of benidipine in the vicinity of MRONJ-like lesions can promote osteonecrotic extraction socket healing.